Intraoperative Inducibility of Atrial Fibrillation Does Not Predict Early Postoperative Atrial Fibrillation - Lanters, Eva A. H. (J Am Heart Assoc, 2018)
BACKGROUND: Early postoperative atrial fibrillation (EPoAF) is associated with thromboembolic events, prolonged hospitalization, and development of late PoAF (LPoAF). It is, however, unknown if EPoAF can be predicted by intraoperative AF inducibility. The aims of this study are therefore to explore (1) the value of intraoperative inducibility of AF for development of both EPoAF and LPoAF and (2) the predictive value of de novo EPoAF for recurrence of LPoAF. METHODS AND RESULTS: Patients (N=496, 75% male) undergoing cardiothoracic surgery for coronary and/or valvular heart disease were included. AF induction was attempted by atrial pacing, before extracorporeal circulation. All patients were on continuous rhythm monitoring until discharge to detect EPoAF. During a follow‐up period of 2 years, LPoAF was detected by ECGs and Holter recordings. Sustained AF was inducible in 56% of patients. There was no difference in patients with or without AF before surgery (P=0.159), or between different types of surgery (P=0.687). In patients without a history of AF, incidence of EPoAF and LPoAF was 37% and 2%, respectively. EPoAF recurred in 58% patients with preoperative AF, 53% developed LPoAF. There were no correlations between intraoperative inducibility and EPoAF or LPoAF (P>0.05). EPoAF was not correlated with LPoAF in patients without a history of AF (P=0.116), in contrast to patients with AF before surgery (P<0.001). CONCLUSIONS: Intraoperative AF inducibility does not predict development of either EPoAF or LPoAF. In patients with AF before surgery, EPoAF is correlated with LPoAF recurrences. This correlation is absent in patients without AF before surgery.